2012
DOI: 10.1177/0960327111432502
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the protective effect of flaxseed oil on cisplatin-induced hepatotoxicity

Abstract: Cisplatin (CP) is known as one of the most potent chemotherapeutic antitumor drugs. The tissue-specific toxicity of CP in the kidneys is well documented. However, at higher doses less common toxic effects such as hepatotoxicity may arise. Since CP remains one of the most effective antineoplastic drug used in chemotherapy, strategies to protect tissues against CP toxicity are of clinical interest. Recently, ω-3 polyunsaturated fatty acids (PUFAs) from certain plants/seeds notably flaxseed have shown numerous he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 48 publications
7
31
0
2
Order By: Relevance
“…These results are in agreement with the study reported by Naqshbandi et al [51]. This observation is consistent with a recent report by Yadav, (2015) that showed CDDP administration induced significant increase in serum ALT, AST and significant decrease in serum total protein, and albumin levels [30].…”
Section: Influence Of L-arginine On Cisplatin-induced Hepatotoxicity supporting
confidence: 94%
“…These results are in agreement with the study reported by Naqshbandi et al [51]. This observation is consistent with a recent report by Yadav, (2015) that showed CDDP administration induced significant increase in serum ALT, AST and significant decrease in serum total protein, and albumin levels [30].…”
Section: Influence Of L-arginine On Cisplatin-induced Hepatotoxicity supporting
confidence: 94%
“…That's to say, one of the mechanisms about cisplatininduced liver injury is oxidative damage. Naqshbandi A et al (2012) showed that dietary supplementation of flaxseed oil in cisplatin-treated rats ameliorated cisplatininduced hepatotoxic and other deleterious effects due to its intrinsic biochemical/antioxidant properties (Naqshbandi A et al, 2012). Gaona-Gaona L et al (2011) investigated the protective effect of sulforaphane pretreatment against cisplatin-induced liver and mitochondrial oxidant damage in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that hepatic and renal GPx activity in tumor-bearing mice and CIS treated mice significantly decreased as compared to normal control. These results may be explained based on that CIS exerts its toxic effects by inducing the generation of ROS which can interact with cellular membranes to cause lipid peroxidation, and thereby alter the structure and function of membranes [30].…”
Section: Discussionmentioning
confidence: 99%